Sosialisasi dan Pendampingan Islamic Parenting Ibu Keren Generasi Alpha di Era Digital di SPS As-Sa’diyyah Gondang Pace Nganjuk - M. Burhanuddin Ubaidillah; Hafidhul Umami; Masduki Masduki (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
The quality of good parenting is the ability of parents to monitor all children's activities so that when the child is down, parents can provide support and treat children well, according to their child's condition. Based on the results of interviews, in Gondang village there are several problems related to the lives of children due to their inability to filter culture from globalization, which can damage the morale of the nation's generations, especially children. The approach method used in socializing counseling and mentoring is Asset Based Community Development (ABCD), namely a community service approach that utilizes existing assets. The results of the Socialization & Assistance of Islamic Parenting for Cool Mothers in Generation Alpha Families in the Digital Age at SPS As-Sa'diyyah Gondang Village, Pace District, Nganjuk Regency show an increase in the knowledge of mothers in raising children in the digital era, especially in terms of using gadgets , limiting children's time when playing gadgets. After this program, mothers hope that the parenting program can be held again every year (beginning/end of the year) with different parenting materials, both in the form of seminars and practices such as mamamia competitions which can increase the closeness between children and mothers.